PERAN LEMBAGA KUA DALAM MEMBERIKAN PENDIDIKAN PRANIKAH SEBAGAI UPAYA PENCEGAHAN PERNIKAHAN DINI - Hakim, Muh. Luqmanul; Radino; Sabarudin; Muharraddinsyah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
Premarital education is an effort to provide knowledge related to various materials about marriage. The KUA of Kempo sub-district has made various efforts in providing premarital education to the community as an effort to prevent early marriage. This study aims to analyze the role of the Kempo Sub-district KUA in providing premarital education to the community, and evaluate the extent to which this education can prevent early marriage in the area. This research is a descriptive qualitative field research. The data was collected using interview, observation, and documentation techniques. As for data analysis, researchers used data collection techniques, data condensation, data display, and finally conclusions: drawing/verifying. The results showed that some of the roles, strategies and evaluations that have been carried out by the Kempo sub-district KUA in reality have been able to have a good influence on reducing the number of early marriages that occur in Kempo kecematan